Evaluation of microvascular densityby CD34 in squamous cell carcinoma of the tongue and its relationship with cervical lymph node metastasis - Eshghyar N.; Motahhary P.; Rahrotaban S. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: Angiogenesis plays a central role for development and progression of malignant tumors.It is considered as an important factor for predicting of malignant tumor's behavior such as metastasis to lymph nodes and other clinicopathologic factors. However , it is still a controversial factor especially in oral squamous cell carcinoma.The aim of this study was to evaluate the correlation between angiogenesis and clinicopathologic parameters such as presence of metastatic cervical lymph node in the tongue squamous cell carcinoma. "nMaterials and Methods: In this cross-sectional study, 40 cases of squamous cell carcinoma of the tongue were selected from the archive of cancer institute of Tehran University of Medical Science. Sections were prepared from paraffin blocks and immunohistochemically stained with antibody against CD34. Stained vessels were counted in 4 fields ,the most vascular areas at low magnification, in each areas of intratumoral ,peritumoral and nontumoral adjacent tissue in two groups with metastatic lymphnodes (N+) and without (N-). The average counts from the four most vascular areas were recorded as the mean microvascular density (MVD). Data were analyzed by 3wayANOVA and Independent T- test with p<0.05 as the level of significance. "nResults: High mean MVD-CD34 was significantly correlate with positive cervical lymph node metastasis in intra tumoral and peritumoral areas but there was no significant correlation between mean MVD-CD34 and age, gender, and differentiation of tumor. "nConclusion: Based on the results of this study, CD34 can help us to determine the presence of cervical lymph node metastasis and may also determine the outcome of a primary squamous cell carcinoma of the tongue.